UPAYA PEMERINTAH INDONESIA DALAM MENGHADAPI PENYEBARAN ISIS - Bayu Tetuko; Sri Muryantini (Jurnal Studi Diplomasi dan Keamanan, 2016)
The emergence of Islamic State of Iraq and Syria (ISIS) in 2011 has been threatening the traditional state system through it caliphate idea that stretching from Syria through Iraq. Now, the spread of the Islamic State is not only in the Middle East but it has become a worldwide movement since the ISIS expanded into network of affiliates in many countries. The propagate of ISIS has been found in Indonesia marked by Indonesian citizens that joins the ISIS. This paper seeks to investigate Indonesia’s policy to stop ISIS influence. It argues that Indonesia employs soft and hard approaches simultaneously to counter the spread of ISIS.